PROGRAM KKN UNIVERSITAS MATARAM PADA WISATA DANAU DI DESA TUA DI UJUNG UTARA LOMBOK TIMUR: PROGRAM KKN UNIVERSITAS MATARAM PADA WISATA DANAU DI DESA TUA DI UJUNG UTARA LOMBOK TIMUR - Yadnya, Made Sutha; Nurhasanah; Kurniadianto, Dwi; Hajatsyah, Lani Sapitri; Wulandari, Zurrizka Putri; Azminda, Muhammad Azwar Fidar; Kurniawan, Aldhi Putra Ade; Rahayuningsih, Ramdani; Atsani, Affan (Universitas Mataram, 2024)
Tourism is everything related to tourism including the business of tourist objects and attractions and related businesses in the field. Many places in West Nusa Tenggara Province have great potential for tourists to visit. One of the tourist spot located at the northern end of East Lombok is in the old village of Obel-Obel. This village has a tour